High School Students to IPMI Institute: A Campus Tour & InnoHub - Brian McNerney; Samuel PD Anantadjaya; Irma M Nawangwulan; DC Ethan Samuel; Daniella CE Samuel; Iqbal Surya (Journal of Sustainable Community Development (JSCD), 2025)
This manuscript provides a structured analysis of a community development initiative conducted by students of IPMI Institute, employing a mixed-method evaluative framework grounded in Shared Value theory, Corporate Social Responsibility principles, and Social Capital Theory. The program engaged a local orphanage through targeted interventions, provision of essential goods, structured educational interactions, and operational support, designed to enhance community welfare while strengthening student competencies relevant to contemporary business practice. Methodologically, the initiative was assessed using qualitative observation, stakeholder feedback interviews, and basic output metrics (for instance, beneficiary reach, resource distribution efficiency, and engagement intensity). Findings demonstrate significant gains in students’ applied leadership, cross-functional coordination, and impact assessment capabilities, illustrating the pedagogical effectiveness of experiential social engagement within business education. On the community side, the program contributed to incremental capacity-building, improved resource accessibility, and strengthened relational networks consistent with Social Capital development. The results underscore the strategic value of embedding community-oriented initiatives within business curricula to generate dual outcomes: enhanced student readiness for impact-driven organizational environments and measurable community-level benefits aligned with sustainable development objectives.